The Effect of the Buteyko Breathing Technique on Asthma Control in Asthma Patients - Munthe, Eliska Epriana Katarina; Oktarina, Yosi; Sari, Yulia Indah Permata (Jurnal Ilmiah Ners Indonesia, 2026)
Asthma is a chronic non-communicable disease that cannot be cured but can be managed through pharmacological and non-pharmacological strategies. This study aimed to determine the effect of the Buteyko breathing technique on asthma control among asthma patients in a primary care setting. A quasi-experimental pre-test and post-test design with intervention and control groups was used. The sample consisted of 42 respondents, with 21 participants in each group, selected using purposive sampling. The intervention group received supervised Buteyko breathing exercises twice a week for four weeks, while the control group received standard care. Asthma control was measured using the Asthma Control Test (ACT). Data were analyzed using paired t-tests and independent t-tests after normality assumptions were assessed. The intervention group showed a significant improvement in ACT scores after the Buteyko breathing intervention (mean score increased from 14.38 to 18.95; p < 0.001), while the control group showed no significant change (mean score decreased from 14.19 to 13.81; p = 0.088). The post-test ACT score was significantly higher in the intervention group than in the control group (p < 0.001), with a moderate effect size (Cohen's d = 0.64). These findings indicate that the Buteyko breathing technique may support asthma self-management and improve asthma control as a complementary non-pharmacological nursing intervention.